Effect of Water Area and Waterweed Coverage on the Growth of Pond-Reared Eriocheir sinensis - Yongcheng Tang; Jiao Peng; Jiahao Chen; Yunlin Zhao; Yi Ding; Jingyi Dai; Zhiyuan Hu; Tian Huang; Meng Dong; Zhenggang Xu (Fishes, 2022)
Water area and waterweed coverage are the key environmental factors for ecological breeding of Eriocheir sinensis in ponds. In order to explore the effects of above two factors on the growth of E. sinensis, three groups of experiments were set up: low coverage small area (C1S1), high coverage small area (C2S1), and high coverage large area (C2S2), and water environmental factors and the growth of E. sinensis were monitored. The results showed that the dissolved oxygen of ponds with different waterweed coverage was significantly different (p < 0.05), and the phosphate in ponds changed significantly from July to October (p < 0.05). The correlation analysis showed that NH3-N and pH were significantly positively correlated (p < 0.05). At the same time, there was a significant negative correlation between NH3-N and DO, H3PO4 and pH (p < 0.05). Further analysis of the relationship between surface area, waterweed coverage and environmental factors revealed that the surface area and waterweed coverage were closely related to NH3-N, H3PO4 and DO. From July to October, the differences in morphology and weight of E. sinensis in different ponds became more and more significant. In terms of growth rate, C1S1 with a small area and low coverage had a downward trend, while C2S1 and C2S2 were the opposite. In the final stage of the experiment, C2S2 had the highest yield (0.1311 kg/m2), and C1S1 had the lowest yield (0.0600 kg/m2). Then, the ponds with high waterweed coverage and large area can bring better benefits.